Integration of ecotheological values in the islamic education curriculum in the era of ecological crisis - Raghusfi Bhuena Ventura; Mohamad Johan Saril; Moch Nasikin; Dimas Sari Martasila; Uswatun Khasanah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The global ecological crisis demands a paradigm shift in the world of education, including in Islamic Education. This article aims to examine in depth the integration of ecotheological values ​​in the Islamic Education curriculum as a response to environmental challenges. This study uses a qualitative approach through literature study, with an analysis of the green curriculum, ecologically oriented verses of the Qur'an, and literature on Islamic education and environmental theology. The results of the study indicate that Islamic teachings contain strong ecotheological principles, such as the concepts of tauhid, amanah, mizan, and khalifah. The integration of these values ​​into the Islamic Education curriculum can be done through the formulation of learning objectives, development of teaching materials, and pedagogical methods based on ecological action. Thus, an ecotheologically oriented curriculum is able to instill spiritual awareness and ecological responsibility in students.